The Role of Nitric Oxide on Histamine H3 Receptors Mediated Rat Gastric Fundus Contractile Responses (Annals of Medical Research, 2021)
None
Keywords: Histamine H3 receptor, Nitric oxide, Gastric fundus (R)-Α-Methylhistamine, Contractility, Electrical field stimulation.